Extrahepatic biliary obstruction impairs microvascular perfusion and increases leukocyte adhesion in rat liver - Koeppel, Thomas; Trauner, Michael; Baas, Jens; Thies, Jochen; Schlosser, S. F.; Post, Stefan; Gebhard, Martha-Maria; Herfarth, Christian; Boyer, James L.; Otto, Gerd (Hepatology, 1997)
To determine if disturbances of the liver microcirculation may be of pathophysiological relevance for liver damage during acute biliary obstruction, we studied the effects of bile duct ligation (BDL) on hepatic microhemodynamics and leukocyte adhesion in rat liver in vivo. Male Wistar rats were subjected to BDL for 3 days and 7 days, respectively. Sham-operated controls underwent laparotomy without BDL. After 3 days, intravital fluorescence microscopy (IVM) and hydrogen gas (H2) clearance were performed to study hepatic microvascular perfusion. Furthermore, leukocyte-endothelial cell interactions were assessed by IVM. Intercellular adhesion molecule 1 (ICAM-1) protein expression was studied by Western blot analysis and tissue immunofluorescence after 3 and 7 days, respectively. Analysis of microvascular perfusion by IVM revealed a marked impairment of sinusoidal perfusion after 3 days. Assessment of H2 clearance confirmed that overall hepatic microvascular perfusion was decreased. In addition, increased leukocyte adhesion in sinusoids and venules could be observed. A concomitant increase of ICAM-1 expression in liver tissue was also noted within the first week after BDL. Our results show that BDL is followed by a marked depression of the hepatic microcirculation and increased leukocyte adhesion in vivo within 3 to 7 days. Together, these findings suggest that deficits in microvascular perfusion and increased neutrophil infiltration may represent a potential source of liver injury during acute biliary obstruction.